Operational Risk management of Production in PDAM Semarang City - Adityoso, Raden Gunung; Nugroho, Anggoro Budi (Journal of Business and Management, 2015)
Abstract - Risks is the part of human life. Everybody in this world cannot avoid risks. Every activities always connected and associated to the risks. Even its small thing like walking in pedestrian has risk like falling or tripping or big thing like government policy, which is related to lives of many people. One that associated in the lives of many people is water, water cannot be separated from human life because every person in the world needs water to live. One of the companies that provide clean water for people is PDAM or Perusahaan Daerah Air Minum. PDAM is local owned company that has function to supply clean water for citizen of the region, in this case is city. Semarang City also has its own PDAM to meet the needs of its residents of clean water. In carrying out its function, PDAM Semarang also cannot be separated from risks. One of the main part in PDAM Business is production. Without production, PDAM Semarang will not be able to provide clean water for Semarang City residents. This study has three objectives, to determine, analyze and mitigate the operational risks in production of PDAM Semarang especially in Water Treatment Installation 1 who served in Sampangan, Semarang. The results of this study can be used as material for evaluation for PDAM Semarang to face these kind of risks in the future so the company can minimize the impact and losses of the risks. The method used in this study is Monte Carlo Simulation. This analysis is used to predict potential probability and severity of each risk. The probability and severity of each risks simulated compared to the probability and severity for the past 4 years. By comparing the risks simulated and history risks, the writer can determine whether the risk have major impact or not for production. The results reveal that some risks have low probability and severity such as flooding, high water turbidity, production machines problems, red raw water, sedimentation and blackout. These risks can be accepted and retained by PDAM Semarang City because they got low impact. Risk that has high probability and low severity is high cost employee when holiday, this risk recommended to be transferred to contractor or outsourcing company so PDAM doesnâ€™t get impact anymore. For the risk that has high probability and severity is pipe distribution leak will be recommended to be reduced. Â Key words: Operational risk management, Monte carlo simulation, PDAM Semarang City, Risk mitigation